HUBUNGAN ANTARA LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PADA KARYAWAN RESTAURANT DI KABUPATEN JEMBRANA - Putu, Ayu Agustina Paramadhyani; I Gde Dhika , I Gde Dhika; Hartika, Listiyani Dewi (JURNAL PSIKOLOGI MANDALA, 2025)
Abstrak. This study aims to determine whether there is a relationship between the work environment and work motivation in restaurant employees in Jembrana. There are 2 dimensions of the work environment that are measured, namely the Physical and Non-Physical work environment and the motivation theory used is the theory of motivation from Mc Clleland, in which there are three needs, namely achievement, affiliation, and power needs. Data collection was conducted online through WhatsApp groups involving 80 restaurant employees in Jembrana. The method used is quantitative method and uses the Spearman Rho correlation technique with the help of the SPSS version 22 application. In this study, it was found that there was a significant correlation between the work environment and work motivation where the significance of the work environment from each dimension of work motivation obtained was 0.00 which means that the result is <0.05 and there is a correlation coefficient result of 0.549 in the work environment and achievement work motivation, 0.722 in the work environment and affiliation work motivation, and 0.419 in the work environment and power work motivation which based on the Correlation Interval table the results obtained in the work environment test and achievement and power work motivation fall into the medium category, while in the work environment test and affiliation work motivation fall into the strong category.